Reimagining ICT from Within: A Reflective Case Study of Grassroots Digital Transformation in Uganda - Okoed, Martin; Samerson-Thomas, Nadezna; Isabirye, Christopher; Walimbwa, Michael (Jurnal Pendidikan dan Profesi Keguruan, 2026)
Objective: This study aimed to examine how a grassroots Information and Communication Technology (ICT) initiative, developed and sustained by teachers in a resource-constrained secondary school in Uganda, transformed pedagogical practices, institutional culture, and administrative efficiency. This study also sought to conceptualize a hybrid framework for ICT adoption that explains how teacher-led innovation supports sustainable institutional transformation in low-resource educational settings. Methods: This study employed a reflective narrative approach grounded in autoethnographic and participatory inquiry traditions. Data were collected from multiple sources, including workshop reports, stakeholder testimonies, institutional documents, and external recognition records. Data analysis followed Braun and Clarke’s six-phase thematic analysis framework. To ensure methodological rigor and trustworthiness, the study applied triangulation, member checking, collaborative coding, and audit trail procedures. Results:  The findings identified four key dimensions of institutional change: (1) relational leadership and a trust-based culture that strengthened collaboration and shared responsibility; (2) capacity building that enhanced teacher identity and digital competence; (3) improved operational efficiency through the implementation of an automated reporting system; and (4) sustainability supported by teacher ownership and external validation. Quantitative indicators confirmed substantial improvements in administrative performance, including reduced processing time, fewer calculation errors, decreased reporting delays, and increased teacher autonomy in managing digital tasks. Novelty: This study proposes a hybrid ICT adoption model that integrates innovation diffusion, adult learning, and distributed leadership theories. The novelty of this study lies in demonstrating that sustainable ICT adoption is driven primarily by teacher agency, relational leadership, and institutional culture, extending existing ICT adoption frameworks toward a human-centered and context-sensitive model of educational transformation.